Novel management of cervical necrotising fasciitis in a developing country: case report - Salisu, A.; Adeosun, A.A.; Emma-Nzekwue, N.H.; AbuBakar, Sazaly (Cambridge University Press, 2011)
Objective: We report a rare case of cervical necrotising fasciitis arising from poorly managed acute tonsillitis. Case report: A 23-year-old woman presented with a two-week history of fever and an eight-day history of painful neck swelling. Nine days before presentation, she had received digital manipulation of her throat by a neighbour, which had worsened her throat pain. There was associated progressive generalised neck swelling, odynophagia, dysphagia and dyspnoea. An X-ray of the neck soft tissue showed multiple gas collections. Conclusion: Cervical necrotising fasciitis is rare and usually odontogenic in origin. It is associated with a high mortality rate. Our patient responded to aggressive daily bedside wound debridements and dressings, appropriate intravenous antibiotics and high-protein nutritional support. In this way, exploration under general anaesthesia was avoided, in a developing country with limited facilities.